Covid-19 pandemic research opportunity: Is the Middle East & North Africa (MENA) missing out? (2020)
Background: The Covid-19 pandemic has caused fear and panic worldwide, forcing healthcare systems to disregard conventional practices and adopt innovation to contain the infection and death. Globally, there has been a rapid proliferation of research studies and clinical trials assessing risks, infectivity and treatment. Methods: This review assesses the opportunities and challenges in the Middle East North Africa (MENA) region to engage in the conduct of high quality clinical trials during the Covid-19 pandemic. Results: Opportunities are abundant for conducting clinical trials in MENA countries, including substantial cost savings, academic health centers, integrated health information systems, international accreditation, and international collaborations. Yet, the MENA region has missed out on opportunities to advance patient research during prior infectious disease outbreaks caused by the Severe Acute Respiratory Syndrome, Ebola, and the Middle East Respiratory Syndrome, as evidenced by the lack of concerted research and clinical trials from the region. A large vulnerable population, especially the poor expatriate work force, the current isolation of the health centers, and the lack of an expert network or field trained task force, all contribute to challenges preventing the formation of a pan Arab research enterprise for epidemics. Conclusion: Quality clinical research is critical during public health emergencies to identify treatments and solutions. The efficient conduct of clinical trials requires innovative strategies in research design, approval, and dissemination. Many countries in the MENA region have an opportunity to quickly ramp up research capacity and contribute significantly to the fight against the Covid-19 global threat.